Impact of metformin on disease control and survival in patients with head and neck cancer: a retrospective cohort study - Daniel J. Lee; Caitlin P. McMullen; Andrew Foreman; Shao Hui Huang; Lin Lu; Wei Xu; John R. de Almeida; Geoffrey Liu; Scott V. Bratman; David P. Goldstein (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective A number of in vitro and clinical studies have suggested potential antineoplastic effects of metformin. The impact of this medication on outcomes in head and neck cancer is less clear. Our aim was to determine the effect of metformin on outcomes within our large cohort of head and neck cancer patients with Type II Diabetes (T2DM). Study design Retrospective cohort study. Setting Tertiary Cancer Centre. Subjects and methods A retrospective review of individuals with head and neck squamous carcinoma (HNSCC) and T2DM between January 2005 and December 2011 at Princess Margaret Cancer Centre was conducted. Medication history was obtained from surveys at initial presentation and electronic medical record review. Using Cox regression analyses, the association between metformin use and local, regional and distant failures was explored. Subgroup analyses were conducted for oral cavity, oropharynx and larynx. Results A total of 329 HNSCC patients with T2DM were identified, including 195 metformin users and 134 non-metformin users. Patients were well-matched in terms of clinical, pathologic, and treatment factors. No difference in local, regional, or distant failure was observed between diabetic metformin users and diabetic non-metformin users for the entire cohort or within subgroup analysis for subsite. No difference between the two groups was observed for overall survival, recurrence-free survival, and disease-specific survival at 5 years. Conclusion No association between metformin use and oncologic outcomes were observed in this large cohort of HNSCC patients. Multicenter, prospective studies may be needed to verify previous studies identifying a potential anti-neoplastic effect of this medication.